Exergy analysis of marine waste heat recovery CO2 closed-cycle gas turbine system - Mrzljak, Vedran (Array, 2020)
This paper presents an exergy analysis of marine waste heat recovery CO2 closed-cycle gas turbine system. Based on the operating parameters obtained in system exploitation, it is performed analysis of each system component individually, as well as analysis of the whole observed system. While observing all heat exchangers it is found that combustion gases-CO2 heat exchangers have the lowest exergy destructions and the highest exergy efficiencies (higher than 92%). The lowest exergy efficiency of all heat exchangers is detected in Cooler (51.84%). Observed system is composed of two gas turbines and two compressors. The analysis allows detection of dominant mechanical power producer and the dominant mechanical power consumer. It is also found that the turbines from the observed system have much higher exergy efficiencies in comparison to compressors (exergy efficiency of both turbines is higher than 94%, while exergy efficiency of both compressors did not exceed 87%). The whole observed waste heat recovery system has exergy destruction equal to 6270.73 kW, while the exergy efficiency of the whole system is equal to 64.12% at the selected ambient state. Useful mechanical power produced by the whole system and used for electrical generator drive equals 11204.80 kW. The obtained high exergy efficiency of the whole observed system proves its application on-board ships.